Importance of early fault diagnosis for marine diesel engines: a case study on efficiency management and environment. (1st February 2022) - Karatuğ, Çağlar; Arslanoğlu, Yasin
ABSTRACT : The efficient management of marine vessels ensures that ships could operate smoothly and navigate at the most efficient level. Thus, the environmentally friendly voyage realises with the optimised running cost. Such a management approach could be achieved via a planned and proper maintenance strategy on the critical parts of the marine vessels' combustion engines. Accordingly, in this study, some faults that could occur as a result of insufficient operation are combined in various scenarios and obtained results from the engine room simulator are applied in a realistic navigational route to show the results of the management performed with incorrect operations. Comparative indicator diagrams and exhaust gas outlet temperatures of the simulated scenarios are presented. As a result of the inefficient and faulty operations, in all scenarios, the amount of emission gases emitted to the atmosphere and operating expenses increase in parallel with the rise of fuel consumption.